Desain dan Fabrikasi Mandrel Pada Mesin Filament Winding Fiber Reinforced Plastic Untuk Produksi Packing spacer Pipa di PT. RPC Indonesia - Noviandini Galuh Permatasari; Adi Wirawan Husodo; Dhika Aditya Purnomo (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
PT. RPC Indonesia produces pipes using the filament winding method. The pipe has shipping standards to ensure it reaches its destination safely, so a packing spacer is made as a pipe safety in the shipping process. Currently, the process of making packing spacers is using the hand lay-up method. This is deemed less effective because of the lengthy manual manufacturing process with poor results, and because it takes workers who only focus on making packing spacers. Therefore, a mandrel that functions as concrete was designed to transfer the hand lay-up process to the winding process using a filament winding machine for the production of packing spacers. The Ulrich method is used in the mandrel design process for packing spacers, starting from the requirements, making alternative design concepts, selecting design concepts, and realizing the design. Based on the results of the design concept, the selected design concept is design concept 2. Next, the process of fabrication and testing of the mandrel and the output produced by the mandrel are carried out. It was found that the mandrel was able to produce 18 pieces of DN100 pipe packing spacers in 8 hours. The output or packing spacers produced from the production process with a mandrel using a filament winding machine are able to withstand a load of 3008 kg. The total budget for making mandrels is Rp. 5,847,000. In future research, it is expected to add a silicone filament separator component that is resistant to high temperatures so that the fiber does not slip due to the presence of resin.